GAMBARAN POLA PEMBERIAN ASI DAN MAKANAN PENDAMPING ASI (MP ASI) PADA BAYI SERTA PENGETAHUAN IBU DI DESA BUNURAYA KECAMATAN TIGAPANAH KABUPATEN KARO, SUMATERA UTARA TAHUN 2016 - Evi Sari Ariesta; Zulhaida Lubis; Etti Sudaryati (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2016)
Inappropriate complementary feeding pattern, such as the age of the first giving, texture and frequency can cause many nutritional problems for infants. Appropriate breast feeding and complementary feeding has tightly connection with mother’s knowledge about breast  feeding and complementary feeding. The purpose of this study is to know the breast feeding and complementary feeding pattern and mother’s knowledge in Bunuraya Village, Tiga Panah Subdistric Karo Regency. The study is a descriptive study with cross sectional design. The study is using interview method with questionnaire, and the questions are arrange by the writer and have been tested with validity and reability test. The populations of the study are infants from 0 to 12 months and the samples are taken by total sampling method of 63 infants. And the respondent of te study are the infants’s mother. The analysis was using univariat analysis. The result of the study showed that there are 88,5% whom breast feed at least eight times of 26 infants under six months, and 69,2% have breast feeding at least 10 minutes. The age of the first giving start from under 1 month. Complementary feeding pattern based on infants age, there are 56,1% that is still give breast feeding an appropriate complementary feeding texture, and there are 53,7% that is still breast feeding with appropriate meal and snack frequency. About mother’s knowledge, there are 38,1% who have less knowledge. In order to monitor mother’s knowledge with breast feeding and complementary feeding practical by nutrition employee of the health center collaborated with the village midwife, and the midwife more active to give information and assistance to increase knowledge of expectant mother whom will give birth , continued with information and assistance to infants mother when Posyandu every month. Keyword: breast feeding pattern, complementary feeding, mother’s knowledge.